Utilizing Artificial Intelligence To Enhance The Implementation Of The Standards-Based Curriculum For Teaching Arabic In Senior High Schools In Ghana/ الاستفادة من الذكاء الاصطناعي لتعزيز تنفيذ المنهج القائم على المعاييرلتعليم اللغة العربية في المدارس الثانوية العليا في غانا - Muaz, Murtada Mahmud (Ijaz Arabi Journal of Arabic Learning, 2025)
The new standards-based curriculum for teaching Arabic at the Senior High School (SHS) in Ghana aims to equip learners with 21st-century skills, essential competencies, the knowledge required for lifelong learning, and the necessary linguistic skills. This study seeks to explore the potential of utilizing Artificial Intelligence (AI) to enhance the implementation of the Arabic language curriculum for non-native speakers, focusing on SHS in Ghana as a case study. This stems from the curriculum's need for technological support to ensure its success and facilitate its adoption by teachers. The study employs a descriptive-analytical method to illustrate how AI can support the implementation of the standards-based Arabic language curriculum. It reviews theories and practical applications that leverage AI to guide educational activities and monitor learners' progress in acquiring linguistic skills and competencies. AI stands out for its ability to provide personalized learning experiences tailored to the individual needs of learners based on their pace and learning styles, thereby fostering positive interaction within the learning process. Moreover, AI offers precise evaluation models by adapting the difficulty level of questions to learners' actual performance, ensuring appropriate challenges for every learner. The study aims to demonstrate how AI can address diverse learning needs and facilitate the selection of cultural content and educational activities aligned with the standards-based curriculum model, thereby enhancing its implementation.